2000
DOI: 10.1002/1528-2716(200007/09)2:3<335::aid-pse40>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Passive damping technology for buildings in Japan

Abstract: This paper first reviews the concept of the damage‐controlled structure (DCS) which is a kind of passive damping technology, proposed before the Hyogoken‐Nanbu Earthquake in Japan and the Northridge Earthquake in the USA. The philosophy, the necessity and the potential of the damage‐controlled structure are stated in the first two sections of this paper. Second, a modified shear‐bending beam model and a rational dynamic analysis method of three‐dimensional frame for the damage‐controlled structure with passive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 12 publications
0
27
0
1
Order By: Relevance
“…In another study, Papadopoulos P. in 2012 proposed a ne w metal frictional device, the capacity of a restricted rotation around the horizontal axis perpendicular to the vert ical frame plane, in order to increase the seismic capacity of multi-storey planar reinforced concrete (r/c) frames [4]. Another way to protect braced frames is by using buckling restrained braced frames, as it has the same load deformation behavior in both compression and tension and higher energy absorption capacity with easy adjustability of both stiffness and strength [5,6]. In addition, many researchers have proposed the use of post tensioning tec hnology, in braced frames or in moment resisting frames, for residual drift reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Papadopoulos P. in 2012 proposed a ne w metal frictional device, the capacity of a restricted rotation around the horizontal axis perpendicular to the vert ical frame plane, in order to increase the seismic capacity of multi-storey planar reinforced concrete (r/c) frames [4]. Another way to protect braced frames is by using buckling restrained braced frames, as it has the same load deformation behavior in both compression and tension and higher energy absorption capacity with easy adjustability of both stiffness and strength [5,6]. In addition, many researchers have proposed the use of post tensioning tec hnology, in braced frames or in moment resisting frames, for residual drift reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the test results, design guidelines and examples have been developed to mitigate the structural response of frames mounted with mild steel dampers (Tsai et al, 2009;Kurokawa et al, 1998), and some successful applications have been made and reported (Wada et al, 2000;Perry et al, 1993;Yasushi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The cyclic behavior option for the existing buildings [9,10]. A comprehensive of steel braces subjected to reversed compressive and study of damage controlled structures was performed by tensile force exhibits poor energy dissipation due to the Wada et al [11]; they have presented its potential to buckling limit. The energy dissipation or damage design new constructions and retrofit existing structures.…”
Section: Introductionmentioning
confidence: 99%